2009
DOI: 10.1186/1750-1172-4-25
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent microdeletion at 17q12 as a cause of Mayer-Rokitansky-Kuster-Hauser (MRKH) syndrome: two case reports

Abstract: Background: Mayer-Rokitansky-Kuster-Hauser syndrome (MRKH) consists of congenital aplasia of the uterus and the upper part of vagina due to anomalous development of Müllerian ducts, either isolated or associated with other congenital malformations, including renal, skeletal, hearing and heart defects. This disorder has an incidence of approximately 1 in 4500 newborn girls and the aetiology is poorly understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(121 citation statements)
references
References 20 publications
5
115
0
1
Order By: Relevance
“…Recently, two additional patients have been reported by Dixit et al (Dixit et al, 2012), with variable neurocognitive involvement. Very interesting, rarely dysmorphic features for these patients have been documented (Bernardini et al, 2009;Moreno-De Luca and SGENE Consortium, 2010). Thus, with the evidence reported to date, the 17q12 deletions seem to be responsible for a wide range of phenotypes with considerable variability in expressivity and penetrance.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Recently, two additional patients have been reported by Dixit et al (Dixit et al, 2012), with variable neurocognitive involvement. Very interesting, rarely dysmorphic features for these patients have been documented (Bernardini et al, 2009;Moreno-De Luca and SGENE Consortium, 2010). Thus, with the evidence reported to date, the 17q12 deletions seem to be responsible for a wide range of phenotypes with considerable variability in expressivity and penetrance.…”
Section: Discussionmentioning
confidence: 64%
“…Mutational analysis of LHX1 gene has been performed as already reported in Bernardini et al (Bernardini et al, 2009).…”
Section: Mutational Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates HNF1B as a candidate gene for Mayer-Rokitansky-Küster syndrome, as was suggested in publications preceding the description of genital abnormalities in renal cysts and diabetes syndrome. 30 Hypospadia and other genital abnormalities are sporadically described in male individuals. These may be coincident findings, or they may be part of the CAKUT spectrum described above, in which HNF1B mutations are the most commonly identified genetic cause.…”
Section: Genital Tract Malformationsmentioning
confidence: 99%
“…Such observations have placed WNT4 forward in the group of genes thought to be responsible for proper organization of the female sexual organs. Unfortunately, detailed screening for mutations of some genes in MRKH patients initially failed to identify any consistent alteration which could be regarded as causative (Bernardini et al, 2009). Subsequent work (Ledig et al, 2011) found three regions (1q21.1, 17q12, and 22q11.21) of particular interest, suggesting that deletions and/or missense mutations in LHX1 and HNF1B are also strong gene candidates in MRKH.…”
Section: Pgs and Mrkh: Unanswered Questionsmentioning
confidence: 99%